Persepsi Masyarakat Tentang Swamedikasi: Studi Kualitatif Dengan Theory of Planned Behavior - Agusta Ari Murti Kristiyanti; Aris Widayati (Jurnal Farmasi Indonesia, 2022)
ABSTRACT Self-medication is prevalent in the community. However, self-medication also leads to inappropriate symptom identification, unsuitable selected medicines, and incorrect use of medicines. This study aims to explore perceptions about self-medication behavior among people in the community. This research was conducted with a qualitative approach. Respondents were people in Semawung Daleman, Kutoarjo, Purworejo, Central Java. Data were obtained by interviews conducted with a structured interview guide, compiled based on the Theory of Planned Behavior (TPB) framework. The questions involved behavioral beliefs, normative beliefs, and control beliefs to self-medicate. The data were analyzed by content analysis. A total of 25 respondents were interviewed. This qualitative study revealed that self-medication is believed to be easy, fast, and suitable for dealing with health complaints (Behavioural Beliefs). Family members supported self-medication (Normative Beliefs). Lack of knowledge about medicines inhibited self-medication (Control Beliefs). Based on these findings, further research is needed to explore targeted intervention to improve appropriate self-medication behavior.